Vascular Complications and its Related Factors after Coronary Angiography - M Sedghi Sabet; G Benvan; M Baghaie; Z Atrkar- Roshan; M Khalili (Iran University of Medical Sciences, 2015)
Abstract   Background & Aim: Vascular complications after coronary angiography could lead to serious risks in patients. The present study aimed to determine the incidence of vascular complications and its related factors after angiography.   Material & Methods: This cross-sectional study was done on 400 patients undergoing coronary angiography using consecutive sampling method in Rasht Heshmat Hospital. Data was collected through observation and recording the information (including demographic information, clinical and technical factors and a checklist to assess the vascular complications of the removal site of the sheet) and analyzed by descriptive T-test, Chi-Square and Logistic Regression using SPSS-PC (v. 20).   Results: The majority of the sample were male (59/2%) (59/21 ± 11/9). A total of 24% of patients developed vascular complications and ecchymosis had the highest incidence (71/4%). Multivariate Regression analysisindicated that high blood pressure history (p=0.005), systolic blood pressure before removal of the sheet (p=0/023), anticoagulative drugs (p=0/027), sheet size (p<0/001), the number of attempts to venipuncture (p<0/001) and duration of angiography (p<0/001) predictthe development of vascular complications. Conclusion: With knowledge of thepredictive factors of vascular complications, nurses would be able to prevent complications, prolonged hospitalization and hospital costs.